Risk factors and injury causes in occupational accidents in 8 peruvian provinces - Cardenas, Matlin M. (2020)
Introduction: The occupational accidents in the country are described in a general way, mentioning the type of associated work or the place where they took place, evidencing a sub report of a problem that is not yet solved. Objective: To determine the risk factors associated with the mechanism of injury in occupational accidents of workers in eight provinces of Peru in the period 2000-2014. Methods: Transversal, analytical study of those treated for occupational accidents in the EsSalud Hospital emergency in eight regions of Peru. Results: Out of 45291 occupational accidents, in the multivariate study it was found that falls from height and blows were associated with sex (p < 0.001), age (p < 0.001), head injury (p < 0.025), and chest injury (p < 0),003, only for fall from height), in the upper limbs (p < 0.001, only for fall from height), to work seniority (p = 0.004, only for fall from height), to generate a contusion (p < 0.001) or an injury (p < 0.021). Conclusions: Multiple associations of social and labor variables were found, as well as, of the consequences of having been injured, by a blow or by a fall from structural height.